Long-term monitoring of the human intestinal microbiota composition - Rajilić-Stojanović, Mirjana; Heilig, Hans G. H. J.; Tims, Sebastian; Zoetendal, Erwin G.; de Vos, Willem M. (Environmental microbiology, 2013)
Summary The microbiota that colonizes the human intestinal tract is complex and its structure is specific for each of us. In this study we expand the knowledge about the stability of the subject‐specific microbiota and show that this ecosystem is stable in short‐term intervals (< 1 year) but also during long periods of time (> 10 years). The faecal microbiota composition of five unrelated and healthy subjects was analysed using a comprehensive and highly reproducible phylogenetic microarray, the HITChip. The results show that the use of antibiotics, application of specific dietary regimes and distant travelling have limited impact on the microbiota composition. Several anaerobic genera, including Bifidobacterium and a number of genera within the Bacteroidetes and the Firmicutes phylum, exhibit significantly higher similarity than the total microbiota. Although the gut microbiota contains subject‐specific species, the presence of which is preserved throughout the years, their relative abundance changes considerably. Consequently, the recently proposed enterotype status appears to be a varying characteristic of the microbiota. Our data show that the intestinal microbiota contains a core community of permanent colonizers, and that environmentally introduced changes of the microbiota throughout adulthood are primarily affecting the abundance but not the presence of specific microbial species.